2021
DOI: 10.1186/s12933-021-01257-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of glycemic control on the association of endothelial dysfunction and coronary artery disease in patients with type 2 diabetes mellitus

Abstract: Background We investigated whether glycemic control affects the relation between endothelial dysfunction and coronary artery disease in patients with type 2 diabetes mellitus (T2DM). Methods In 102 type 2 diabetic patients with stable angina, endothelial function was evaluated using brachial artery flow-mediated dilation (FMD) with high-resolution ultrasound, and significant stenosis of major epicardial coronary arteries (≥ 50% diameter narrowing) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 51 publications
2
23
0
Order By: Relevance
“…Another study confirmed this change in myocardial relaxation by cardiac catheterization in patients with DM-complicated NIDCM [ 21 ]. A previous study demonstrated that poor glycemic control is closely related to severe endothelial dysfunction [ 32 ]. Furthermore, hyperglycemia-induced oxidative stress, autonomic deficiency, inflammation, abnormalities in calcium homeostasis, apoptosis, and interstitial fibrosis are also responsible for cardiac remodelling and dysfunction [ 2 , 3 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study confirmed this change in myocardial relaxation by cardiac catheterization in patients with DM-complicated NIDCM [ 21 ]. A previous study demonstrated that poor glycemic control is closely related to severe endothelial dysfunction [ 32 ]. Furthermore, hyperglycemia-induced oxidative stress, autonomic deficiency, inflammation, abnormalities in calcium homeostasis, apoptosis, and interstitial fibrosis are also responsible for cardiac remodelling and dysfunction [ 2 , 3 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it has been demonstrated that diabetes control was associated with the good response of PRP therapy having better results compared with diabetic ED cases with bad diabetic control mostly due to decreased endothelial dysfunction. Several researchers pointed out that good diabetic control has a constructive impact on ameliorating such endothelial dysfunction (Chen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…All pre-infection HbA1c were subcategorized into two groups that include poor and good glycemic control. The study defined poor glycemic control as HbA1c ≥ 7% and good glycemic control as HbA1c ≤ 6.9% [11].…”
Section: Hba1c and Glycemic Groupsmentioning
confidence: 99%